Mengungkap Keberhasilan Tax Amnesty : Studi Kasus pada KPP Pajak Pratama Makassar Utara - Aditya Halim Perdana Kusuma Putra; Munawir Nasir; Andika Prawira Buana (ITB AAS INDONESIA, 2018)
Tax amnesty is the abolition of special tax sanctions in Indonesia regulated in Law no. 11 the year 2016 About tax forgiveness. This research is to know the success of applying tax amnesty to the realization of tax revenue and taxpayer compliance on KPP Pratama Makassar Utara. The result of this research stated that the implication of tax amnesty policy at KPP Pratama Utara Makassar did not succeed in terms of tax target on the realization of tax revenue both in 2016 and 2017, besides that tax amnesty policy at KPP Pratama Makassar Utara also did not raise taxpayer compliance ratio either corporate taxpayers or individual taxpayers in terms of registered taxpayers against taxpayers who report their annual tax returns.